Indirect Effects of COVID-19 Pandemic on Children's Ocular Health (Myopia and Digital Eye Strain): A Narrative Review - Maryam Dourandeesh; Mitra Akbari (Mazandaran University of Medical Sciences, 2022)
Background: The outbreak of COVID-19 has significantly affected people's lives worldwide. Governments have used various measures to contain the spread of the pandemic, including confinement policies that have changed children's lifestyles. Children had to limit their outdoor activities and daily routine to indoor activities. Alternative learning systems, such as online and offline teaching via digital devices have replaced traditional teaching methods. Therefore, children have to spend many hours in front of digital devices. As a natural side effect of the pandemic, these changes may influence children's ocular health who may not be able to complain about these problems as early as adults.  Objectives: This study reviews the literature regarding the effects of the COVID-19 pandemic on children's eye health, including myopia and digital eye strain. Methods: For this narrative review, a comprehensive literature search was performed on December 30, 2021, in Google Scholar, PubMed, and Scopus using the following keywords: "COVID-19," "lockdowns," "children," "ocular health," "eye health," "visual health," "ocular complications," "myopia," " myopia progression," "digital eye strain," "computer vision syndrome," "quarantine," and "prevention." A total of 22 eligible studies were identified for review. Results: Studies performed during the COVID-19 pandemic have shown an increase in myopia prevalence, incidence, and progression in children, especially among young children. Strategies imposed by governments to control the spread of COVID-19 during confinement have led to dramatic changes in children's lifestyles. These measures have compelled children to restrict outdoor activities and increase their near-work time (e.g., online e-learning), which contributes to the increase in digital eye strain and myopia progression. Conclusions: Children's eye health can be influenced by the COVID-19 outbreak. These can serve as a warning to policymakers, health professionals, teachers, parents, and children about the effects of pandemics, such as COVID-19, on children's visual health and the need to implement preventive and therapeutic measures.